The Evolving Interstellar Medium of Star Forming Galaxies Since z=2 as Probed by Their Infrared Spectral Energy Distributions - Magdis, G; Daddi, E; Bethermin, M; Sargent, M; Elbaz, D; Pannella, M; Dickinson, M; Dannerbauer, H; Cunha, E; Walter, F; Rigopoulou, D; Charmandaris, V; et al. (2012)
Using data from the mid-infrared to millimeter wavelengths for individual galaxies and for stacked ensembles at 0.5<z<2, (a_co)="" (m*),="" (mdust)="" (mgas="" (ms)="" (sfe)="" (sfr)="" (ssfr="SFR/M*)" -z),="" <u="" a="" a_co="" an="" and="" are="" at="" between="" by="" co-to-h2="" compared="" confirm="" constrain="" content,="" conversion="" correlation="" derive="" distant="" driven="" dust="" efficiencies="" equivalently="" estimates="" exploiting="" factors="" fall="" field,="" for="" formation="" fractions.="" galaxies="" galaxies,="" galaxies.="" gas="" hardness="" high="" higher="" in="" infrared="" large="" like="" local="" lower,="" luminosities.="" magnitude="" main="" mass="" masses="" massive="" mdust="" measurements="" metallicity="" ms="" ms,="" obey="" of="" order="" our="" outside="" radiation="" rate="" rates="" redshifts="" relation.="" relatively="" respectively,="" robust="" samples,="" sequence="" sfe="" show="" specific="" star="" star-bursting="" statistical="" stellar="" that="" the="" these="" those="" tight="" to="" use="" using="" values="" variations="" varying="" we="" which="" with="" within="">, which is proportional to the dust mass weighted luminosity (LIR/Mdust), and the primary parameter defining the shape of the SED, is equivalent to SFE/Z. For MS galaxies we measure this quantity, , showing that it does not depend significantly on either the stellar mass or the sSFR. This is explained as a simple consequence of the existing correlations between SFR-M*, M*-Z and Mgas-SFR. Instead, we show that (or LIR/Mdust) does evolve, with MS galaxies having harder radiation fields and thus warmer temperatures as redshift increases from z=0 to 2, a trend which can also be understood based on the redshift evolution of the M*-Z and SFR-M* relations. These results motivate the construction of a universal set of SED templates for MS galaxies which vary as a function of redshift with only one parameter, .</z<2,>